Budgeting for the poor - Robinson, Mark, 1951- (Basingstoke [England] ; New York : Palgrave Macmillan, 2008)
"Civil society organisations play an increasingly important role in analysing government budget policies and in advocating for more transpa rent and inclusive budget processes in transitional and developing coun tries. Drawing on case studies of six budget groups across Europe, Afri ca, Asia and Latin America, this book is the first comprehensive study of the impact and significance of civic initiatives aimed at enhancing budget transparency and the poverty focus of government expenditure pri orities. Achievements include improvements in the transparency of budge tary decisions, increased budget awareness and literacy, and deeper eng agement in the budget process on the part of legislators, the media and civil society organisations. The case studies in this book show how bu dget groups produce greater equity in budget policies and strengthen de mocracy by fostering accountability, enhancing transparency and deepeni ng participation and voice."--BOOK JACKET.
1. Improving Transparency and Promoting Accountability: Civil Societ y Budget Work in Perspective / Mark Robinson -- 2. Analysing Applied Bu dget Work: Case Studies and Method / Mark Robinson -- 3. Budget Analysi s and Social Activism: DISHA and the Budget Process in Gujarat, India / Laura Malajovich and Mark Robinson -- 4. Democratising the Budget: Fun dar's Budget Analysis and Advocacy Initiatives in Mexico / Mark Robinso n and Vinod Vyasulu -- 5. Budget Work and Democracy-Building: The Case of IBASE in Brazil / Paolo de Renzio and Jim Shultz -- 6. Sustained Wor k and Dedicated Capacity: IDASA's Experience in Applied Budget Work in South Africa / Helena Hofbauer -- 7. Croatia and the Institute for Publ ic Finance: Budget Work in a Transitional Democracy / Albert van Zyl an d Jim Shultz -- 8. Budget Monitoring as an Advocacy Tool: The Uganda De bt Network / Paolo de Renzio, Vitus Azeem and Vivek Ramkumar -- 9. Conc lusions: The Impact and Significance of Applied Budget Work / Mark Robi nson -- 10. Implications for Policy and Practice / Paolo de Renzio and Warren Krafchik.
Includes bibliographical references (p. 213-216) and index.
Keywords: Budget -- Developing countries; Budget process -- Developing countries -- Evaluation; Poverty -- Government policy -- Developing countries; Non-governmental organizations -- Developing countries